1995
DOI: 10.1111/j.1745-9125.1995.tb01174.x
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Various Perspectives on the Intergenerational Transmission of Domestic Violence*

Abstract: Past research indicates that adults who were subject to severe physical discipline as children are often violent toward their spouse and children as adults. This association is usually attributed to modeling or the learning of attitudes that legitimate hitting family members. Using four waves of data from a sample of midwestern families, this study found only limited support for these explanations. Analysis showed that the relationship between childhood exposure to harsh parenting and recurrent adult violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
104
0
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 47 publications
9
104
0
5
Order By: Relevance
“…Specifically, poor and harsh parenting practices have been found to predict adolescent antisocial behavior (Dishion, French, & Patterson, 1995), which shows significant stability into adulthood (Wiesner, Kim, & Capaldi, 2005); and adult antisocial behavior has been found to predict harsh and inconsistent discipline and poor supervision of the subsequent generation (Capaldi & Clark, 1998;Patterson & Capaldi, 1991), as well as problem behavior in the subsequent generation via negative discipline (e.g., Patterson & Dishion, 1988). Adolescent antisocial behavior has been identified recently as a potential mediator in the transmission of parenting practices (e.g., Capaldi et al, 2003;Hops et al, 2003).The links between adolescent antisocial behavior and later poor parenting have been established (Patterson & Capaldi, 1991;Serbin & Karp, 2003;Simons, Wu, Johnson, & Conger, 1995) and, in general, implicate the myriad developmental failures associated with problem behavior (e.g., Capaldi & Stoolmiller, 1999), as well as an accumulating burden of risk that young parents carry as they form families of procreation. Furthermore, the risk that problem behavior confers to parents and children may be compounded through the welldocumented phenomenon of assortative partnering (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, poor and harsh parenting practices have been found to predict adolescent antisocial behavior (Dishion, French, & Patterson, 1995), which shows significant stability into adulthood (Wiesner, Kim, & Capaldi, 2005); and adult antisocial behavior has been found to predict harsh and inconsistent discipline and poor supervision of the subsequent generation (Capaldi & Clark, 1998;Patterson & Capaldi, 1991), as well as problem behavior in the subsequent generation via negative discipline (e.g., Patterson & Dishion, 1988). Adolescent antisocial behavior has been identified recently as a potential mediator in the transmission of parenting practices (e.g., Capaldi et al, 2003;Hops et al, 2003).The links between adolescent antisocial behavior and later poor parenting have been established (Patterson & Capaldi, 1991;Serbin & Karp, 2003;Simons, Wu, Johnson, & Conger, 1995) and, in general, implicate the myriad developmental failures associated with problem behavior (e.g., Capaldi & Stoolmiller, 1999), as well as an accumulating burden of risk that young parents carry as they form families of procreation. Furthermore, the risk that problem behavior confers to parents and children may be compounded through the welldocumented phenomenon of assortative partnering (e.g.…”
mentioning
confidence: 99%
“…The links between adolescent antisocial behavior and later poor parenting have been established (Patterson & Capaldi, 1991;Serbin & Karp, 2003;Simons, Wu, Johnson, & Conger, 1995) and, in general, implicate the myriad developmental failures associated with problem behavior (e.g., Capaldi & Stoolmiller, 1999), as well as an accumulating burden of risk that young parents carry as they form families of procreation. Furthermore, the risk that problem behavior confers to parents and children may be compounded through the welldocumented phenomenon of assortative partnering (e.g.…”
mentioning
confidence: 99%
“…Oftentimes these characteristics consequently play a role in the formation of insecure adult attachments characterized by fear of abandonment, jealousy, distrust, and anger, which are known predictors of intimate partner violence (Dutton, 1998). Other studies have found that interparental violence is often associated with poor parenting ability and harsh treatment during childhood, which may lead to antisocial personality traits and the perpetration of domestic violence in adulthood (Simons, Wu, Johnson, & Conger, 1995). Given this prior literature, I expected to find significant interactions between family-of-origin violence and personality characteristics among offenders in the current study.…”
Section: Length Of Incarcerationmentioning
confidence: 79%
“…Though identifying the specific social structures that facilitate IPV may be key to understanding and effectively intervening in abusive behavior (Michalski, 2004), individuals often come in contact with these structural features that encourage or discourage violent confrontation with intimate others within more proximal contexts, specifically, their social networks. Patterns of abusive behavior may be transmitted through familial (Capaldi & Clark, 1998;Simons, Wu, Johnson & Conger, 1995) or peer (Brown & Messman-Moore, 2010;Browning, 2002;Dishion, Patterson & Griesler, 1994;Erickson, 1988;Schwartz & DeKeseredy, 1997) influences;…”
Section: Resultsmentioning
confidence: 99%